The psychometric properties of the Lithuanian version of ASEBA adult forms - Šimulionienė, R.; Brazdeikienė, L.; Rugevičius, M.; Gedutienė, R.; Žakaitienė, A. (Psichologija, 2010)
ASEBA Adult Forms are designed to obtain information about the adaptive and maladaptive functioning of 18–59-aged adults and to facilitate comparisons between people’s perceptions of their own functioning and other people’s perceptions of their functioning. This article presents the major psychometric properties of Syndrome scales of the Lithuanian version of ASEBA Adult forms developed to evaluate behavioral and emotional problems. ASRs (Adult Self-Report) were administered to 18–59-aged adults comprising a random sample drawn from the whole Lithuania (N = 600). ABCL (Adult Behavior Checklist) forms were completed by people nominated by the participants (spouses, partners, friends etc.). After excluding ASRs and ABCLs of participants who reported mental health and substance use problems or did not respond to more than 8 items, the remaining 510 forms were used in data analysis. Four issues were examined: 1) the internal consistency of the forms, 2) item–total correlations, 3) cross-informant agreement, and 4) correlations between scales. Data analysis showed adequate psychometric properties of Syndrome scales. Cronbach’s alphas ranged from 0.62 to 0.95 for different ASR and ABCL scales. The Anxious / Depressed and Aggressive Behavior scales had the highest level of internal consistency, and the Thought Problems scale had the lowest alpha in both forms. The cross-informant correlations ranged from 0.36 for the Thought Problems to 0.61 for the Anxious / Depressed scale. The mean of the Q correlations between 0–1–2 scores on the problem items of ASRs and on the counterpart items of ABCLs was 0.51, indicating the moderate level of agreement between different informants. Correlations between scales confirmed the proposed structure of both forms and derivative scales (Internalizing, Externalizing, and Total Problems). Differences between Lithuanian and USA samples were most strongly expressed among 18–35-aged females and 36–59-aged males. The majority of scale scores in the Lithuanian sample were higher than in the USA sample. The effect size of the differences between Lithuanian and American samples was moderate for most of the scales. Future research is needed to improve the psychometric properties of the Lithuanian version of ASEBA Adult forms.
Keywords: behavioral and emotional problems; reliability and validity of ASEBA Adult forms